Psallus jungaricus sp. n.—a new species of plant bugs from Xinjiang (Western China) (Hemiptera: Heteroptera: Miridae: Phylinae) - Vinokurov, Nikolai N.; Luo, Zhaohui (Zootaxa, 2012)
Psallus (Psallus) jungaricus Vinokurov et Luo, sp. n., is described from northern Xinjiang (Western China, basin of theEerqisi River and Jungarian Alatau). The new species can be distinguished by the absence of a red pattern on the dorsum,and only the abdominal tergite VII in the female with small red spots. It is similar to the Euro-Siberian Psallus haematodes(Gmelin, 1790) and the Middle Eastern P. galilaeus Linnavuori 1965, and also pale specimens of the south Euro-AnatolienPsallus anaemicus Seidenstücker, 1966 in having a pale cuneus; but it differs from these species in the color pattern of the dorsum and the structure of the male genitalia.